Effect of Boron and Sowing Dates on the Nutrients Concentration and Uptake in Wheat (Triticum aestivum) (The Agriculturists, 2010)
The effect of boron and different dates of sowing on some wheat cultivars was studied at BAU farm during winter season of 2006-07. There were two boron treatments (0 and 1 kg B ha-1), three wheat cultivars (Prodip, Shatabdi and Sourav) and four sowing dates (18 November, 28 November, 08 December and 18 December, 2006). The experiment was conducted in a split-split plot design in the three replications. The grain samples were analyzed for N, P, K and B, while the straw samples were analyzed for P, K and B contents and uptake. Both N and B concentrations of grain were significantly increased by boron application.